APSColombia, the best ally of the European Union in the implementation of the EUDR - Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma. (Federación Nacional de Cultivadores de Palma de Aceite, Fedepalma, 2024)
APSColombia, Sustainable Palm Oil from Colombia, is an initiative that contributes to consolidating our sustainable origin and making Colombia and the world aware of the efforts of thousands of palm oil producers who strive every day to bring out a unique and differentiated oil.
Keywords: Palma de aceite; Sostenibilidad; Colombia; APSColombia; Principios; Unión europea